Edukasi Lingkungan dan Pemberdayaan Masyarakat melalui Inovasi Plang Edukasi Waktu Penguraian Sampah sebagai Upaya Meningkatkan Kesadaran Lingkungan di Dusun Pasar Hilir - Mila Fitria Amanda; Amellia Zahratul Syahlu; Iznillah Lutifyah Husna; Jeffry Juliana; Zico Riski Putra; Donal Syafrianto (Lembaga Pengembangan Kinerja Dosen, 2026)
Waste management has become a critical environmental issue at both global and national levels due to increasing population and changing consumption patterns. In Indonesia, waste generation exceeds 60 million tons annually, with a significant portion consisting of plastic waste that requires hundreds of years to decompose. One of the main challenges in addressing this issue is the low level of public awareness and understanding regarding waste types and their decomposition time. This community service program conducted by students of Universitas Negeri Padang aims to improve environmental awareness through environmental education and community empowerment using an innovative visual medium in the form of waste decomposition time educational boards. The activity was implemented in Pasar Hilir Hamlet, Lumindai Village, using a participatory approach involving observation, socialization, board design, production, and installation. The results indicate that the program successfully enhanced community knowledge regarding the differences between organic and inorganic waste and their environmental impacts. The educational boards, placed in strategic locations near waste disposal areas, function as effective visual tools that continuously deliver information and reinforce environmentally responsible behavior. In addition, this program contributes to improving environmental cleanliness, strengthening community participation, and increasing environmental literacy. Therefore, the innovation of waste decomposition time educational boards serves not only as an informative medium but also as a sustainable educational tool to promote long-term behavioral change toward environmental awareness.